Crystallisation temperature control of stoichiometry and selectivity in host–guest compounds. Issue 44 (2nd November 2017) - Sykes, Nicole M.; Su, Hong; Weber, Edwin; Bourne, Susan A.; Nassimbeni, Luigi R.
Abstract : Correction for 'Crystallisation temperature control of stoichiometry and selectivity in host–guest compounds' by Nicole M. Sykes et al., CrystEngComm, 2017, 19, 5892–5896.